Faktor-Faktor Yang Memengaruhi Pemanfaatan Aplikasi Desktop Pemeriksaan di Lingkungan Direktorat Jenderal Pajak - Arihatsu, Comera; Ariyanto, Dodik; Sudana, I Putu; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi; Vol 32 No 6 (2022)DO - 10.24843/EJA.2022.v32.i06.p02, 2022)
This study aims to examine the factors that influence the utilization of the Examination Desktop application (Derik) by combining the technology acceptance model (TAM) and social cognitive theory. The research sample was 320 tax examiners spread across all work units of the Directorate General of Taxes in Indonesia which were selected by purposive sampling technique. The data analysis tool used is SEM-PLS. The results showed that perceived convenience and perceived usefulness had a positive effect on user attitudes that led to the use of the Derik application. Meanwhile, computer self-efficacy, result expectations, feelings and user readiness increase user utilization in the use of the Derik application by tax examiners. The results also show that user anxiety has a negative effect on the tax examiner's utilization of the Derik application. Keywords: Social Cognitive Theory; TAM; Derik's Application.